2018
DOI: 10.1042/bcj20170672
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of a splicing factor through a nuclear kinase–kinase complex

Abstract: The splicing of mRNA is dependent on serine-arginine (SR) proteins that are mobilized from membrane-free, nuclear speckles to the nucleoplasm by the Cdc2-like kinases (CLKs). This movement is critical for SR protein-dependent assembly of the macromolecular spliceosome. Although CLK1 facilitates such trafficking through the phosphorylation of serine-proline dipeptides in the prototype SR protein SRSF1, an unrelated enzyme known as SR protein kinase 1 (SRPK1) performs the same function but does not efficiently m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 44 publications
3
45
0
Order By: Relevance
“…New light has been shed on this by two recent studies that show that SRPK1, after being localized to the nucleus, facilitates the dissociation of SRSF1 from the nuclear speckles by the formation of an SRPK1-CLK1 complex. The presence of SRPK1 facilitates the release of SRSF1 from CLK1 and enhances further phosphorylation of SP dipeptides, resulting in the mobilization of SRSF1 from nuclear speckles to nucleoplasm (50,51). In this study, we observed that SRPK2 also plays a role in the mobilization of SRSF3 from the speckles to nucleoplasm.…”
Section: Phosphorylation Mechanisms Of Sr Proteinssupporting
confidence: 55%
“…New light has been shed on this by two recent studies that show that SRPK1, after being localized to the nucleus, facilitates the dissociation of SRSF1 from the nuclear speckles by the formation of an SRPK1-CLK1 complex. The presence of SRPK1 facilitates the release of SRSF1 from CLK1 and enhances further phosphorylation of SP dipeptides, resulting in the mobilization of SRSF1 from nuclear speckles to nucleoplasm (50,51). In this study, we observed that SRPK2 also plays a role in the mobilization of SRSF3 from the speckles to nucleoplasm.…”
Section: Phosphorylation Mechanisms Of Sr Proteinssupporting
confidence: 55%
“…We now wished to identify regions in the RS domain that may be responsible for this change in subnuclear mobility. Because we showed previously that CLK1-dependent phosphorylation of several Ser-Pro dipeptides in the C-terminal polypeptide segment of the RS domain (RS2) induces a hyperphosphorylation state that releases SRSF1 from speckles (16,17), we speculated that dephosphorylation of serines at the other end of the RS domain (RS1) (Fig. 6A) might be responsible for the hypophosphorylated state that also releases the SR protein from speckles (Fig.…”
Section: Several Serines In the Rs Domain Regulate Srsf1 Speckle Occumentioning
confidence: 95%
“…Cho et al (4) demonstrated that RRM1 of SRSF1 interacts with an RRM from the U1-70K subunit of U1 snRNP, thus facilitating assembly of the early spliceosome. In a recent study, RRM1 was shown to serve as a platform for PP1 binding and activity control, although the molecular contacts for this interaction were not defined (17). Because these findings highlight the importance of RRM1 as a protein interaction module, we performed experiments to define the molecular nature of the PP1-RRM interface within an SR protein and uncover potential links to mRNA processing events.…”
Section: Pp1 Binding To Splicing Factor Srsf1mentioning
confidence: 99%
See 2 more Smart Citations